Inside Cover: Interaction with Ribosomal Proteins Accompanies Stress Induction of the Anticancer Metallodrug BOLD‐100/KP1339 in the Endoplasmic Reticulum (Angew. Chem. Int. Ed. 10/2021). Issue 10 (1st February 2021) - Neuditschko, Benjamin; Legin, Anton A.; Baier, Dina; Schintlmeister, Arno; Reipert, Siegfried; Wagner, Michael; Keppler, Bernhard K.; Berger, Walter; Meier‐Menches, Samuel M.; Gerner, Christopher
Abstract : A multi‐omics approach including proteomics, transcriptomics, and imaging was applied to comprehensively investigate the mode of action of the anticancer ruthenium(III) drug candidate BOLD‐100. In their Communication on page 5063, Samuel M. Meier‐Menches, Christopher Gerner, and co‐workers found the ribosomal proteins RPL10, RPL24, and the transcription factor GTF2I as probable protein targets. They are functionally connected to endoplasmic reticulum stress, a key drug effect of BOLD‐100.